Pengaruh Harga, Kualitas Produk, dan Promosi Terhadap Pengambilan Keputusan Pembelian Pada Online Shop Shopee (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis 2018 Universitas Islam Malang) - Widiana Saskia Putri; N. Rachma; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine how much influence price, product quality, and promotion have on purchasing decisions at shopee online shop. This type of research uses exsplanatory research with a quantitative approach. The population in this study was Unisma's Feb 2018 students, totaling approximately 950 students. The sampling technique used with the Malhotra formula used the number of indicators multiplied by 5, the target number was 115 respondents. The data analysis methods used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, F test, T test, coefficient of determination, to analyze the data using the spss 16 application. The results of this study indicate that the variable price, product quality, and promotion have a positive and significant effect simultaneously on purchasing decisions, the results of this study also show that partially the price variable has no effect on purchasing decisions, while partially the product quality and promotion variables have a significant and positive effect. on purchasing decisions at shopee online shop. Keywords : Price, Product Quality, Promotion, Buying Decision